Collaborative pathways: UiTM’s journey to open science initiative / Wahidah Mohd Zain - Mohd Zain, Wahidah (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2024)
In March 2023, Information Science Studies, College of Computing, Informatics and Mathematics, Universiti Teknologi MARA (UiTM) Negeri Sembilan Branch, Rembau Campus embarked on a transformative journey with the launch of the "Open Science Readiness in Malaysian Academic Institutions" project. This pivotal initiative, in partnership with Paula Lackie, a seasoned Fulbright Specialist from Carleton College, MN, USA, was a strategic move to fortify the academic infrastructure with research data management (RDM) and open science principles, thanks to the Fulbright Specialist Program which facilitated this international collaboration.